Kesedihan Tokoh Utama dalam Kumpulan Puisi Karya Anne Bronte - Icha Choirunisa Herawan (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2023)
The title of this research is Kesedihan Tokoh Utama dalam Kumpulan Puisi Karya Anne Bronte. The aims of this research is to find the representation the sadness of the main character who described by Anne Bronte in her collection poems through the deep structure of the poem which includes; theme, tone, feeling and mandate. The method of this research is qualitative descriptive. The approach of this research is literary objective approach. The result of this research show the sadness of the main characters who described in the Anna Bronte collection poems are caused by logging, loneliness and losing which through by the main characters itself of their lives.